A comprehensive multidisciplinary care pathway for hip fractures better outcome than usual care?. Issue 7 (July 2021) - Flikweert, Elvira R.; Wendt, Klaus W.; Diercks, Ronald L.; Izaks, Gerbrand J.; Stewart, Roy; Stevens, Martin; Reininga, Inge H.F.
Highlights: This study will contribute to the very sparse evidence of the benefit of comprehensive care pathways for hip fractures in the long term. Functional outcome 6 months after hip fracture treatment is the same for patients treated in a care pathway or with usual care. For patients with a hip fracture treated in a care pathway, the hospital stay is shorter, making a care pathway probably cost-effective. It is difficult to get long term (functional) results in studies including frail elderly patients; statistics can help. Abstract: Introduction: Hip fracture surgery is among the most performed surgical procedures in elderly patients. Mortality rates are high, however, and patients often fail to live independently following a hip fracture. To improve outcome, multidisciplinary care pathways have been initiated, but longer-term results are lacking. Aim of this study was to compare functional outcome and living situation six months after hip fracture treatment with and without a care pathway. Patients and methods: A multicentre prospective controlled trial was conducted with three hospitals: in one hospital patients were treated with a care pathway, in the other hospitals patients received usual care. All patients aged ≥ 60 years with a hip fracture were asked to participate. Besides basic characteristics, health-related quality of life (EQ-5D) and performance scores of activities of daily living (Katz Index and Lawton IADL) were assessed. Differences in scores were analysed using linear regression. Propensity score adjustment was used to correct for differences between the care pathway and the usual care group. Missing data were imputed. Results: No differences in rate of return to prefracture ADL level were found between patients in the care pathway group and the usual care group. The percentage of participants in the same situation as before the fracture was the same in both treatment groups (81%). There were no significant differences in quality of life, activities of daily living or mortality (15% vs 10%, p  = 0.17), but hospital stay in the care pathway group was significantly shorter (median 7 vs 10 days). Discussion: Treatment of elderly patients with a hip fracture is commonly organised in care pathways. Although short-term advantages are reported, positive effects on longer-term functional results could not be proven in our study. This study confirmed a shorter hospital stay in the care pathway group, which potentially may lead to a reduction in costs. Conclusions: Functional outcome and living situation six months after a hip fracture is the same for patients treated with or without a care pathway.